2010
DOI: 10.1063/1.3529236
|View full text |Cite
|
Sign up to set email alerts
|

Propulsive force measurements and flow behavior of undulatory swimmers at low Reynolds number

Abstract: The swimming behavior of the nematode Caenorhabditis elegans is investigated in aqueous solutions of increasing viscosity. Detailed flow dynamics associated with the nematode's swimming motion as well as propulsive force and power are obtained using particle tracking and velocimetry methods. We find that C. elegans delivers propulsive thrusts on the order of a few nanonewtons. Such findings are supported by values obtained using resistive force theory; the ratio of normal to tangential drag coefficients is est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
131
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(148 citation statements)
references
References 49 publications
17
131
0
Order By: Relevance
“…However, the sinusoidal waveform is typically a theoretical model, which may inevitably introduce deviations from the reality. Our findings 8 and prior research 2,9 have shown that C. elegans tends to vary its swimming gait in response to the ambient viscosity. Nevertheless, the same theory was later adopted by some research groups to study the nematode neurobiology and behavior 10 phenotype.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, the sinusoidal waveform is typically a theoretical model, which may inevitably introduce deviations from the reality. Our findings 8 and prior research 2,9 have shown that C. elegans tends to vary its swimming gait in response to the ambient viscosity. Nevertheless, the same theory was later adopted by some research groups to study the nematode neurobiology and behavior 10 phenotype.…”
Section: Introductionsupporting
confidence: 53%
“…A medium with viscosity of 10 mPa s was made by mixing dextran (FL-95771/MW ¼ 2 000 000, Sigma) with the NGM buffer to achieve a 6% dextran solution. Numerous studies 2,8,9,31 have reported that C. elegans is able to sense the ambient viscosity change and make a behavioral response according to the coordination between sensory and motor neurons. A representative trajectory of movement and a relationship of power and propulsion similar to the previous N2 and kin-2 are depicted in Figs.…”
Section: Effects Of Strain and Liquid Viscosity To Motility Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The subscripts U, S, and C denote, respectively, the contributions of the undulatory motion, background flow, and steric Lennard-Jones-like hindrance. We compute M(t), F U,x (t), F U,y (t), F S,x (t), (24,25). As the swimmer approaches the side wall, its head enters a region of low velocity while its tail remains exposed to a higher velocity (t = 2 s).…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Swimming of AL-fed and DR wild-type worms was also determined as a function of the mechanical load using viscous liquids, in which the worms require greater muscle strength to maintain their locomotory rate (Sznitman et al, 2010). Taking into account that DR-fed C. elegans display an ~60% lower protein content, most likely a proxy for muscle mass, than AL-fed worms (Fig.…”
Section: Research Articlementioning
confidence: 99%